Structural evolution in Pt/Ga-Zn-oxynitride catalysts for photocatalytic reforming of methanol. (November 2016) - Vass, ÿdám; Pászti, Zoltán; Bálint, Szabolcs; Németh, Péter; Szíjjártó, Gábor P.; Tompos, András; Tálas, Emília
Graphical abstract: Highlights: ⿢ Wurtzite-like Ga-Zn-oxynitrides were obtained from oxide mixtures and precipitates. ⿢ Pt/Ga-Zn-oxynitrides were active in methanol photocatalytic reforming reaction. ⿢ Pt co-catalyst obtained by calcination had higher activity than that by reduction. ⿢ Ga-Zn-oxynitrides transformed to oxyhydroxides during the photocatalytic reaction. ⿢ In situ metallic Pt formation was observed during the photocatalytic reaction. Abstract: Products of microwave-assisted urea-induced co-precipitation of Ga(NO3 )3 and Zn(NO3 )2 or Ga2 O3 and ZnO were nitridated in order to obtain Ga-Zn-based photocatalysts. Irrespectively to the starting material, wurtzite-like Ga-Zn-oxynitride phases formed. The preparation was completed by deposition of a Pt co-catalyst, which was activated by either reduction in hydrogen or calcination in air. It was demonstrated by X-ray diffraction (XRD), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) that during oxidative activation the oxynitride started to transform into a nitrogen-free Zn-containing Ga- oxyhydroxide. Regardless to the structure of the catalysts after the activation step, almost complete oxynitride to oxyhydroxide transformation was observed during the methanol photocatalytic reforming reaction, accompanied by complete reduction of the Pt co-catalyst to metallic state. The observations of this study point to the importance of phase transitions under reaction conditions in the development of the active ensemble in the Ga, Zn-based photocatalysts.